Metal cation-exchanged zeolites with the location, state, and size of metal species controlled. Issue 44 (28th April 2020) - Osuga, Ryota; Bayarsaikhan, Saikhantsetseg; Yasuda, Shuhei; Manabe, Ryo; Shima, Hisashi; Tsutsuminai, Susumu; Fukuoka, Atsushi; Kobayashi, Hirokazu; Yokoi, Toshiyuki
Abstract : Controlling the location, state, and size of metal species in the metal cation-exchanged zeolites has been achieved using the framework Al distribution-controlled MFI -type zeolites. Abstract : Rh ion-exchanged MFI -type aluminosilicate zeolites with different Al distributions were prepared for controlling the location, state, and size of Rh species. The MFI -type aluminosilicate zeolite with the framework Al atoms predominantly located inside the channel intersections leads to the formation of relatively large Rh species, which were confirmed by ultraviolet-visible (UV-vis) and infrared (IR) spectroscopies. Moreover, this catalyst showed a high catalytic activity for the oxidative reforming reaction of methane.